Analisis Penguatan Karakter Menuju Era Society 5.0 Melalui Pendidikan Pancasila dan Kewarganegaraan Di Sekolah Dasar (International Forum of Researchers and Lecturers, 2024)
The Society 5.0 era is a new era that is a development of the 4.0 revolution era. This new era has positive and negative impacts with all the shopistication of digital technology. In an effort to minimize the negative impact of Society 5.0 Era, one of the things that can be done is to foster and strengthen the character of the younger generation through Pancasila and Citizhenship Education. This will help the younger generation to face technological advances armed with a sense of nationalism and Pancasila values. In this case, the role of parents and teachers is very important in shaping the character of the younger generation, in this case, students in elementary school. By using a good method, it will make the delivery to students easier to understand and implement.